2018
DOI: 10.1039/c8ra02606h
|View full text |Cite
|
Sign up to set email alerts
|

Transfer hydrogenation of aldehydes catalyzed by silyl hydrido iron complexes bearing a [PSiP] pincer ligand

Abstract: The synthesis and characterization of a series of silyl hydrido iron complexes bearing a [PSiP] pincer ligand were reported. These complexes showed good to excellent catalytic activity for transfer hydrogenation of aldehydes under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…It must be noted that the addition of Lewis acid played an important role for this catalytic process. These results demonstrate that this catalytic system has good tolerance for some substituents and the catalytic conditions are milder than other Lewis acid‐promoted system, with shorter reaction time or lower reaction temperature …”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…It must be noted that the addition of Lewis acid played an important role for this catalytic process. These results demonstrate that this catalytic system has good tolerance for some substituents and the catalytic conditions are milder than other Lewis acid‐promoted system, with shorter reaction time or lower reaction temperature …”
Section: Resultsmentioning
confidence: 74%
“…Complexes 1–3 were prepared according to the literature procedures . Complex 4 was obtained from the combination of bis( o ‐(diisopropylphosphino)phenyl)methylsilane with Fe (PMe 3 ) 4 in THF at 0 °C under Ar atmosphere (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to the isoelectronic P-donor sites, the silyl anion sites possess a stronger trans effect and create electron-rich metal centers that are amenable to application in catalysis. , In seminal work, Stobart et al used bis­(phosphinoalkyl)­silanes, such as [R 2 P­(CH 2 ) n ] 2 SiMeH ( I , n = 2, 3), as precursors for the preparation of pincer complexes between the related ligand I′ and metals, such as Pt, Ir, and Ru (Scheme ). It was later shown that these ethylene- and propylene-bridged ligands I′ are rather flexible, rendering the metal complexes kinetically labile, which tentatively precluded any applications in catalysis. , Thus, the more rigid bis­( o -phosphinophenyl)­silanes [R 2 P­( o -C 6 H 4 )] 2 SiMeH ( II ) have been frequently used in reactions with metals, such Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, and Au, which in most cases (except Cu, Au) provided stable pincer complexes with the related ligand II′ . The ethylene-bridged pincer ligands I′ ( n = 2) and II′ are expected to create bonding situations with similar P–M–P bite angles due to the same number of bridging carbon atoms. Many of these pincer complexes were formed via oxidative addition across the Si–H bonds and feature activated M–H bonds and have found diverse applications in catalysis, including for instance the reduction of carbon dioxide or transfer hydrogenation reactions. …”
Section: Introductionmentioning
confidence: 99%
“…[15] We reported the transfer hydrogenation of aldehydes catalyzed by silyl hydrido iron complexes bearing a [PSiP] pincer ligand under mild conditions in moderate to good yields. [16] In comparison with Rh, Ru and Fe complexes, the study on Ni complexes as homogeneous catalysts for transfer hydrogenation of carbonyl compounds is relatively less. Ojwach and coworkers studied that ((pyrazolyl) ethyl)pyridine Ni (II) complexes could catalyze the transfer hydrogenation of ketones in iso-propanol at 82°C affording conversions of 58-84% within 48 hr.…”
Section: Introductionmentioning
confidence: 99%